Prevalence and outcome of hospitalised patients with unexplained hyperkalaemia at a tertiary centre in South Africa - Ndinya, Florentius; Chothia, Mogamat-Yazied (African Journal of Nephrology, 2025)
Background: Hyperkalaemia is frequently encountered in hospitalised patients and is associated with high morbidity and mortality. There is a lack of data on the prevalence and outcomes of hospitalised patients with unexplained hyperkalaemia in Africa. This study aimed to address this knowledge gap. Methods: We conducted a retrospective cohort study of all adult patients hospitalised with hyperkalaemia, defined as a potassium concentration of ≥5.5 mmol/L, between 1 January 2019 to 31 December 2019. Patients with kidney disease, rhabdomyolysis, tumour lysis syndrome, or who were taking medications that interfere with renal potassium elimination were excluded. Results: Hyperkalaemia prevalence was 8.2% (184/2256). The median age of the patients was 40 years (interquartile range: 30–56), and 67% were men. In-hospital death was 8%, with no difference in potassium concentration between patients who died or were discharged alive (5.8 mmol/L vs 5.7 mmol/L, P=0.11). Only older age (adjusted odds ratio: 1.04; 95% confidence interval: 1.01–1.08) was associated with in-hospital death. There was no association between in-hospital death and potassium concentration range on survival analysis (P=0.85). Regression analysis revealed associations between potassium concentration and leukocyte counts in patients requiring emergency surgery and those with haematological disorders. A blood gas was performed in 17%, with a mean laboratory-to-blood gas potassium concentration bias of +1.3 mmol/L. Insulin therapy was prescribed in 7% with one episode of hypoglycaemia. Conclusion: Unexplained hyperkalaemia was associated with low in-hospital deaths. We speculate that the elevated potassium concentrations were spurious and likely due to preanalytical errors.